Pentecostalism and the land grab in Cerro de Pasco (1958-1967) - Julcarima Álvarez, Gerson Francisco (2005)
Almost everything that I will discuss below is essentially based on the commendable work of Serafín Nieto Chamorro, a person who was commissioned in 1997 to record the biographies of the first Pentecostal leaders of Cerro de Pasco. The misfortunes of my life have prevented me to date from knowing him personally, but I still appreciate him, despite the fact that I only know of him his work called Historia del evangelio en la Quebrada de Chaupihuaranga (Daniel Alcides Carrión province), department of Pasco.